Kepuasan Pelanggan Dalam Berbelanja di Alfamidi Pagelaran Bogor - Efrita Norman; Zul Hiskandar; Evinovita Evinovita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
This study aims to analyze the effect of price and location on Alfamidi's customer satisfaction in Pagelaran Village, Bogor. The method used is descriptive and associative quantitative analysis, data collection used in this study using primary data sourced from questionnaires distributed to customers of Alfamidi Raya Ciomas who are in Pagelaran Village. Sampling using the saturated sample technique where the sample is consumers who have shopped at Alfamidi in the performance village. The sample used was 100 Alfamidi customer respondents in Pagelaran Village. Based on the results of the study showed that 1) price had a positive and significant effect on customer satisfaction, 2) location had a positive and significant impact on customer satisfaction, 3) price and location together had a positive effect on customer satisfaction. positive and significant impact on customer satisfaction in shopping for Alfamidi customers in Pagelaran Village.